(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Diffuse Axonal Injury (DAI) is a pervasive and debilitating consequence of traumatic brain injury (TBI), representing a primary determinant of mortality and long-term neurological disability. Historically conceptualized as immediate mechanical tearing of axons, DAI is now understood as a progressive pathophysiological process initiated by rotational and acceleration-deceleration forces, leading to widespread white matter disruption. Gross pathology may reveal subtle hemorrhages in the corpus callosum and brainstem, while microscopic examination identifies axonal swelling, retraction bulbs, and eventual secondary axotomy. Molecular mechanisms include calcium influx, calpain-mediated cytoskeletal degradation, mitochondrial dysfunction, and Wallerian degeneration. Immunohistochemical markers, such as Amyloid Precursor Protein (APP), facilitate early detection, and advanced neuroimaging modalities—including Diffusion Tensor Imaging (DTI)—enable in vivo assessment of axonal integrity. Chronic changes involve demyelination, gliosis, and neuroinflammation, with long-term functional outcomes determined by network disconnection and residual neuronal reserve. Understanding DAI’s pathological anatomy is essential for prognostication, clinical management, and development of neuroprotective interventions.